The uses and gratifications of using Facebook : a study of Palestinian students in the International Islamic University Malaysia - Alakklouk, Bader N. A. (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The study explores the uses and gratifications (U & G) theory of the use of Facebook among Palestinian students at the International Islamic University Malaysia (IIUM). The study is premised on U & G theory, which posits that individuals actively choose media or media content to satisfy their needs. In this study, IIUM Palestinian students provide their perspective towards the uses and gratifications of using Facebook as they experience living abroad. In-depth interviews were conducted with 12 Palestinian students in IIUM because they are heavy users of Facebook Palestinians and students of the IIUM. Facebook is the most convenient platform to express ideas and opinions on the crisis of Palestine. Therefore, the number of Palestinian users on Facebook has increased significantly due to the Palestine-Israel conflict that is taking place in the West Bank, Gaza Strip and Jerusalem. This qualitative research study is to contribute in terms of examining student perception and how their needs could be gratified by Facebook and why the Social Networking Site (SNS) gratifies their needs. All participants in this study use Facebook actively in their daily life. The study proposed three research questions: (1) What needs of IIUM Palestinian students are gratified by Facebook? (2) Why does Facebook gratify the needs of IIUM Palestinian students? and (3) How could Facebook improve its features in gratifying the needs of IIUM Palestinian students? The Palestinian students were selected based on specific criteria: 1) IIUM students in Gombak, 2) Palestinian citizens and 3) active Facebook users. The participants were also between 23 and 32 years old, had one account on Facebook each, had been using Facebook for 5-10 years and had been visiting Facebook daily for 1-8 hours per day. The findings of the study identify the needs of participants that are gratified by Facebook as follows: connecting, source of news and information, freedom of expression, entertainment and academic purposes. The results also find the reasons why Facebook gratifies IIUM Palestinian students' needs. This is because SNS is perceived as a convenient platform, it is a famous SNS, it provides entertainment and allows the freedom of expression. In addition, the participants in this study pointed out three improvements that are required from Facebook that will motivate them to use the SNS in order to satisfy more needs: improving the privacy of users, reducing advertisements and allowing more freedom to express themselves.